КАДРОВА ПОЛІТИКА НА МИТНИХ УСТАНОВАХ ПІВДЕННОЇ УКРАЇНИ В ОСТАННІЙ ЧВЕРТІ XVIII ñ ПЕРШОМУ ДВАДЦЯТИРІЧЧІ ХІХ ст. (Zaporizhzhia Historical Review, 2021)
The article analyzes personal management at customs in Southern Ukraine (1775 ñ 1819), the level of customs employees training, of providing customs with specialists, and of working conditions on the basis of the original sources.